Konsep Kepemimpinan Pemerintahan Transformational-Servant Leadership - Aminah, Sitti (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2017)
The Indonesia nation faces a leadership crisis. Most people lose strong leadership figures and leaders who can be role models. The purpose of the study was describe the transformational leadership model and the servant leadership model. The qualitative approach wasused by examining various literature sources, namley: books, international scientific journals and research results. The literature review results were described transformational leadership model and servant leadership models, the difference between both leadership models and hot wo combine those models in leadership research area.